Religious categories and the construction of the indigenous - Hartney, Christopher. (Supplements to Method & Theory in the Study of Religion, 2016)
This volume significantly advances the academic debate surrounding the taxonomy and the categorisation of 'indigenous religion'. Developing approaches from leading scholars in the field, this edited volume provides the space for established and rising voices to discuss the highly problematic topic of how indigenous 'religion' can be defined and conceptualised. Constructing the Indigenous highlights the central issues in the debate between those supporting and refining current academic frameworks and those who would argue that present thinking remains too dependant on misunderstandings that arise from definitions of religion that are too inflexible, and from problems caused by the World Religion paradigm. This book will prove essential reading for those that wish to engage with contemporary discussions regarding the definitions of religion and their relations to the indigenous category.